Karakterisasi Bionanofiller Dari Limbah Serbuk Kayu Meranti Sebagai Pengisi Pada Polimer Komposit - Maria Ulfah; Sri Aprilia; Fauzi M. Djuned (Fakultas Teknik, 2018)
Utilization of wood powder is one of the alternative in waste wood prevention which has not been optimally utilized. Utilization of bionanofiller based on wood waste such as wood powder can also reduce dependence on raw materials such as silica, clay, bentonite, zeolite which diminished its existence. The sample used in this study is Meranti wood powder which is then prepared and characterized. The characterization of bionanofiller waste of Meranti wood powder is done by analyzing particle density, XRD, SEM, and FTIR. Particle density analysis showed Meranti wood powder having density of 0,044 gr/cm . XRD analysis shows that the maximum peak at an angle of 2θ = 22,2o 3 indicates the presence of carbon phase. The results of SEM analysis of Meranti wood powder are suitable for use as fillers because they are 1 μm in size. The result of functional group analysis shows the presence of functional groups -OH, -CH3, -CH2, C = C, C-H and C-O.